Unsteady MHD Free Convective Two Immiscible Fluid Flows in a Vertical Permeable Plate with Heat and Mass Transfer under Chemical Reaction and Heat Source - L., Sivakami.; A., Govindarajan; P. Siva, E. (International Journal of Engineering and Technology, 2018)
In this article , the nonlinear Unsteady MHD FreeÂ  convective Two Immiscible Fluid Flows in a vertical Permeable plate with Heat and Mass Transfer under chemical reaction and Heat source have been studied here. The conservation equations are solved analytically under the boundary conditions by using perturbation technique. The influence of various non dimensional parameters namely, Magnetic parameter, Prandtl number, chemical reaction,, Thermal radiation parameter and Schmidt number are examined on the velocity, Temperature, Concentration fields in detail. It is noted thatÂ  the velocity is decreased with increasing Heat source under chemical reaction parameter. But increasing suction parameter decreases the velocityÂ